Design and Implementation of an Automated Hospital Management System with MERN Stack - Jayasiri K.C.N.; Thathsarani W.R.V.K.; De Silva D.I.; Vidhanaarachchi S. (International Journal of Engineering and Management Research, 2022)
A hospital is a place that needs more effective and efficient management of information, people, and assets. This paper demonstrates the design and implementation of an autonomous system with mern stack that can manage doctor information, patient information, inventory information, and administrative functionalities in a hospital environment. This was written with the intention of eliminating the problems of manual hospital management systems such as data redundancy, data inaccuracy, poor accesibility and lack of data security. The paper addressed the problems of time consumption of storing, retrieving, updating, and processing hospital data, generating ambiguous and inaccurate reports, and poor access control to sensitive information in manual paper-based hospital management systems and provides an intuitive and modern approach to solving those problems using an autonomous web application to improve the overall efficiency of a hospital environment. The tools used to implement the proposed system are reactjs library with redux, expressjs, nodejs, and mongodb as the online cloud database. Google oauth 2.0 is used as the authorization protocol. This proposed solution provides an excellent way of authentication and authorization, generating reports for statistical and information gathering purposes, managing administrative tasks, and improving information storing, manipulating and retrieving infrastructure.